Direct interactions between PSD-95 and stargazin control synaptic AMPA receptor number - Schnell, Eric (The National Academy of Sciences, 2002)
Excitatory synapses in the brain exhibit a remarkable degree of functional plasticity, which largely reflects changes in the number of synaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs). However, mechanisms involved in recruiting AMPARs to synapses are unknown. Here we use hippocampal slice cultures and biolistic gene transfections to study the targeting of AMPARs to synapses. We show that AMPARs are localized to synapses through direct binding of the first two PDZ domains of synaptic PSD-95 (postsynaptic density protein of 95 kDa) to the AMPAR-associated protein, stargazin. Increasing the level of synaptic PSD-95 recruits new AMPARs to synapses without changing the number of surface AMPARs. At the same time, we show that stargazin overexpression drastically increases the number of extra-synaptic AMPARs, but fails to alter synaptic currents if synaptic PSD-95 levels are kept constant. Finally, we make compensatory mutations to both PSD-95 and stargazin to demonstrate the central role of direct interactions between them in determining the number of synaptic AMPARs.